1986
DOI: 10.1161/01.str.17.6.1319
|View full text |Cite
|
Sign up to set email alerts
|

Painful tonic spasms caused by putaminal infarction.

Abstract: SUMMARY Lacunar infarcts in the basal ganglia are known to cause various movement disorders, such as chorea, focal dystonia, and hemlchorea-hemiballlsmus. We report here a case of putaminal lacunar infarction which presented with "painful tonic spasms" of the contralateral limbs. This consisted of paroxysmal brief, painful, flexor contractures of the upper, and occasionally the lower limb. These were not focal seizures but were controlled with carbamazepine, which has been used for the "painful tonic spasms" w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…From this finding, they concluded that abnormal hyperactivity of thalamic neurons contributed to the pathophysiology of paroxysmal kinesigenic dyskinesia. There have been several reports that paroxysmal kinesigenic dyskinesia is associated with specific lesions of the thalamus [15,16], putamen [17], right frontotemporal region [18], globus pallidus [19], dorsal medulla oblongata [20] and cervical spinal cord [21]. Sunohara et al [15] reported a necropsied case in which the patient had shown exercise-induced dystonia of the left limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this finding, they concluded that abnormal hyperactivity of thalamic neurons contributed to the pathophysiology of paroxysmal kinesigenic dyskinesia. There have been several reports that paroxysmal kinesigenic dyskinesia is associated with specific lesions of the thalamus [15,16], putamen [17], right frontotemporal region [18], globus pallidus [19], dorsal medulla oblongata [20] and cervical spinal cord [21]. Sunohara et al [15] reported a necropsied case in which the patient had shown exercise-induced dystonia of the left limbs.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age at initial onset was 11.7 ± 3.1 (range [8][9][10][11][12][13][14][15][16][17] years, and the mean disease duration was 6.9 ± 5.1 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14] years. The confirmation of PKC was based on the diagnostic criteria of Kertesz [14].…”
Section: Methodsmentioning
confidence: 99%
“…Tonic spasms may occur in various neurologic disorders, such as cerebral ischemia 15,16 or spinal cord trauma, 11 but they are most commonly associated with MS. The pathologic nature of lesions has not been established, but there is a widely held conviction that TS are related to a localized inflammatory reaction rather than to chronic established areas of demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…1 The attacks are brief, lasting less than 2 minutes, and may occur as frequently stereotyped attacks several times per hour. 1,2 TS are usually associated with multiple sclerosis, 1 but they have been described in various neurologic disorders, such as cerebral ischemia 3,4 and spinal cord lesions. 5,6 Anatomically, TS have also been associated with various cerebral and spinal cord lesions.…”
Section: Dear Professor Kayementioning
confidence: 99%